PENGARUH CUSTOMER PERCEIVED VALUE ACCOR PLUS PROGRAM TERHADAP CUSTOMER LOYALTY DI NOVOTEL TANGERANG - Emma Josephine; Supina Supina (ADISAM PUBLISHER, 2023)
This study aims to analyze the effect of the Accor Plus Customer Perceived Value (CPV) program on Customer Loyalty (CL) at Novotel Tangerang. Researchers used quantitative methods with sampling techniques using Non-Probability Sampling with Purposive Sampling methods. Data collection techniques were obtained from distributing questionnaires to 100 respondents, with a Likert scale measurement scale. IBM SPSS version 25 is used to processed data that have been obtained. Based on data analysis it can be concluded that the results of the validity and reliability tests, it is known that each of the statement indicators has valid and reliable results. In addition, the data used in this study can also be said to be valid through the normality test with a significance value of 0.062. Based on the heteroscedasticity test, no symptoms of heteroscedasticity were found because the significance value was 0.800 > 0.050. Based on the Linearity test, the sig linearity value was 0.001 <0.005, and the sig deviation from linearity value was 0.315 > 0.005 so there is a linear relationship between CPV and CL. In addition, based on the results of the simple linear regression test, it can be seen that the CPV (X) has a positive effect on CL (Y). Where for every 1% increase in the CPV value, the CL value will increase by 0.117. Based on the coefficient of determination test, the CPV variable has the ability to influence the CL variable by 20.1%, while the other 79.9% is influenced by other factors outside the independent variables in this study.As for the advice given in this research, the research object needs to review more of the Accor Plus program. As for the later researchers, it is needed to find deeper references regarding research topics and lastly, the need for seriousness and perseverance in conducting research so that this research can be completed done properly and on time.